Physical properties, structure, and shape of radioactive Cs from the Fukushima Daiichi Nuclear Power Plant accident derived from soil, bamboo and shiitake mushroom measurements. (January 2015) - Niimura, Nobuo; Kikuchi, Kenji; Tuyen, Ninh Duc; Komatsuzaki, Masakazu; Motohashi, Yoshinobu
Abstract: We conducted an elution experiment with contaminated soils using various aqueous reagent solutions and autoradiography measurements of contaminated bamboo shoots and shiitake mushrooms to determine the physical and chemical characteristics of radioactive Cs from the Fukushima Daiichi Nuclear Power Plant accident. Based on our study results and data in the literature, we conclude that the active Cs emitted by the accident fell to the ground as granular non-ionic materials. Therefore, they were not adsorbed or trapped by minerals in the soil, but instead physically adhere to the rough surfaces of the soil mineral particles. Granular Cs* can be transferred among media, such as soils and plants. The physical properties and dynamic behavior of the granular Cs* is expected to be helpful in considering methods for decontamination of soil, litter, and other media.